Analisis Semiotik Puisi Akulah Medan Karya Teja Purnama - Rahmadani, Novia; Ramadan, Gilang; Isman, Muhammad (Universitas Negeri Padang, 2025)
This study analyzes semiotic signs in Teja Purnama's poem